The contribution of fire to the late Miocene spread of grasslands in eastern Eurasia (Black Sea region) - Feurdean, Angelica (Sci Rep, 2019)
Grasslands are globally extensive, but the processes governing their ecology and evolution remain unclear. The role of fire for the expansion of ancestral C(3) grasslands is particularly poorly understood. Here we present the first biomass combustion record based on late Miocene to Pleistocene (~10–1.9 Ma) charcoal morphologies (grass, herbs, wood) from the Black Sea, and test the extent of fire events and their role in the rise of open grassy habitats in eastern Eurasia. We show that a mixed regime of surface and crown fires under progressively colder and, at times, drier climates from the late Miocene to Pliocene (8.5–4.6 Ma) accelerated the forest to open woodland transition and sustained a more flammable ecosystem. A tipping point in the fire regime occurred at 4.3 Ma (mid-Pliocene), when increasingly cold and dry conditions led to the dominance of grasslands, and surface, litter fires of low intensity. We provide alternative mechanisms of C(3) plant evolution by highlighting that fire has been a significant ecological agent for Eurasian grasslands. This study opens a new direction of research into grassland evolutionary histories that can be tested with fossil records of fire alongside climate and vegetation as well as with dynamic vegetation modells.